The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0748233720979278
|View full text |Cite
|
Sign up to set email alerts
|

SAHA attenuates rotenone-induced toxicity in primary microglia and HT-22 cells

Abstract: Rotenone is an industrial and environmental toxicant that has been strongly associated with neurodegeneration. It is clear that rotenone induces inflammatory and oxidative stress; however, information on the role of histone acetylation in neurotoxicity is limited. Epigenetic alterations, neuroinflammation, and oxidative stress play a role in the progression of neurodegeneration and can be caused by exposure to environmental chemicals, such as rotenone. Histone modifications, such as methylation and acetylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Although SAHA did not affect the KHSRP expression, it inhibited the inflammatory response by declining the expression of iNOS, and NF-Κb through STAT3 signalling pathway inhibition. [29,30] Zhang et al [32] reported the prevention of diabetic nephropathy / diabetic kidney progression by MCC950 through NLRP3/ caspase-1/IL-1β pathway prevention or by inhibiting NLRP3 inflammasome stimulation. The inhibition of PI3K activity by quercetin in one-hour time period was also reported in chronic lymphocytic leukaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SAHA did not affect the KHSRP expression, it inhibited the inflammatory response by declining the expression of iNOS, and NF-Κb through STAT3 signalling pathway inhibition. [29,30] Zhang et al [32] reported the prevention of diabetic nephropathy / diabetic kidney progression by MCC950 through NLRP3/ caspase-1/IL-1β pathway prevention or by inhibiting NLRP3 inflammasome stimulation. The inhibition of PI3K activity by quercetin in one-hour time period was also reported in chronic lymphocytic leukaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Three pharmacological inhibitors (SAHA at 1µM, Quercetin at 60µM, and MCC950 1µM) [29][30][31][32][33][34] were tested to explore the activity of these inhibitors on MnCl 2 modulated KHSRP expression.…”
Section: Induction Of Toxicity In N2a Cell Lines By Mnclmentioning
confidence: 99%
“…Finally, the OD values were measured at wavelength of 570 nm. In all viability experiments, 1 μM and 10 μM Rotenone dissolved in DMSO was employed as positive control [ 103 , 104 , 105 ].…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, TSA reduces A β plaques and oligomers by enhancing the phagocytosis of microglia and ameliorates cognitive function in APP/PS1 mice [ 131 ]. Comparably, suberoylanilide hydroxamic acid (SAHA), another pan-HDAC inhibitor, suppresses HDAC activity in microglia and reduces rotenone-induced inflammation and oxidative stress [ 133 ]. Additionally, valproic acid (VPA), a pan-HDAC inhibitor, is documented to exert neuroprotective actions in the rotenone rat model, paving the way for histone acetylation modifications of NDDs [ 134 ].…”
Section: Epigenetic Regulation Of Microglia Function and Phenotypes In Neurodegenerative Diseasesmentioning
confidence: 99%